Create multiple-choice tests based on experimental activities to assess students' 21st century skills in the heat and heat transfer topic - Sherlin Illene; Selly Feranie; Parsaoran Siahaan (Intelektual Pustaka Media Utama, 2023)
Currently, we are facing the rapid development of information and communication technology (ICT) that characterizes the 21st century. Challenges, problems, life, and careers in the 21st century can be successfully faced if we master 21st-century skills. However, nowadays it is still very rare to develop a 21st century skill measurement model, so it is necessary to develop test instruments to measure 21st century skills. The development of test instruments to measure 21st-century skills in Indonesia is still very open, with attention being paid to the clarity of the instrument in describing real phenomena and complete data as material for problem solving. Based on the description above, the researchers developed a multiple-choice test based on experimental activities to measure students’ 21st century skills, which are creativity, critical thinking, collaboration, and communication (4Cs) in heat and heat transfer using research and development (RD) methods with the analyze, design, develop, implement, and evaluate (ADDIE) stage. Development begins with conducting literature and field studies, designing and making videos of experiment activities, compiling open-ended questions, distributing them to 12th graders of science, analyzing answers based on references, developing answer options, developing multiple-choice tests, conducting validation by experts, and testing limited to students. The product of this research is expected to be used by educators and students for independent learning activities or as an example to develop multiple choice tests based on experimental activities to measure 21st century skills in other physics materials and other subjects.